Keberlanjutan UMKM Perempuan: Literasi Keuangan, Inklusi Keuangan dan Fintech - Puspitasari, Ayudia Dwi; Octavini, Nanda Andreas; Setiawan, Yudi; Nuraini, Resti (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2024)
Purpose – This study aims to analyze the role of financial literacy in financial inclusion and its impact on the sustainability of women's MSMEs.Methodology – The population of this study was women who owned MSMEs in Lampung Province. The sample used was 100 women's MSMEs obtained using purposive sampling techniques. The criteria set were: 1) women's MSMEs and 2) MSMEs based on their type of business. Data analysis using SEM PLS.Findings – This study shows that financial literacy and inclusion affect the sustainability of women's MSMEs. While fintech does not affect the sustainability of women's MSMEs. Financial literacy affects financial inclusion, while financial literacy towards fintech and fintech towards financial inclusion has no effect.Originality/Novelty – Combining financial literacy, financial inclusion and fintech on the sustainability of women's MSMEs with various types of MSME businesses and using the SEM PLS method because it is more suitable for causality modelling.Implications – The findings of this study demonstrate the importance of more profound financial literacy education and a more inclusive approach in improving understanding of fintech to encourage the achievement of business sustainability goals. Training and strengthening managerial capacity and economic management based on better understanding will be key in supporting women's MSMEs to be more resilient and sustainable.